2021
DOI: 10.1186/s13089-021-00205-x
|View full text |Cite
|
Sign up to set email alerts
|

The role of point-of-care ultrasound in the diagnosis of pericardial effusion: a single academic center retrospective study

Abstract: Background Symptomatic pericardial effusion (PCE) presents with non-specific features and are often missed on the initial physical exam, chest X-ray (CXR), and electrocardiogram (ECG). In extreme cases, misdiagnosis can evolve into decompensated cardiac tamponade, a life-threatening obstructive shock. The purpose of this study is to evaluate the impact of point-of-care ultrasound (POCUS) on the diagnosis and therapeutic intervention of clinically significant PCE. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 23 publications
1
8
0
1
Order By: Relevance
“…Due to the small sample size, some clinical features may have been over-amplified, so we also included a review of published cases in the literature to overcome these problems. Studies have suggested that the frequency of IIMs with pericardial effusion is 12.37%–17%, 23 which is similar to the 12.2% in this study, and similar to other studies, the patients with pericardial effusion in our collected cases are all small or moderate pericardial effusions (small effusion is 50–100 mL, moderate effusion is 100–500 mL, and large effusion> 500 mL); however, if there is no large amount of pericardial effusion or pericardial tamponade, 7 , 24 27 it is more reliable.…”
Section: Discussionsupporting
confidence: 90%
“…Due to the small sample size, some clinical features may have been over-amplified, so we also included a review of published cases in the literature to overcome these problems. Studies have suggested that the frequency of IIMs with pericardial effusion is 12.37%–17%, 23 which is similar to the 12.2% in this study, and similar to other studies, the patients with pericardial effusion in our collected cases are all small or moderate pericardial effusions (small effusion is 50–100 mL, moderate effusion is 100–500 mL, and large effusion> 500 mL); however, if there is no large amount of pericardial effusion or pericardial tamponade, 7 , 24 27 it is more reliable.…”
Section: Discussionsupporting
confidence: 90%
“…The final research question and search strategy, PRISMA flow diagram, and summary table of the final included studies are shown in tables Q1.1, Q1.2, and Q1.3, respectively. 21 references were represented 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 . The final summary of evidence, assignment of levels of evidence, and GRADE recommendation for this question are shown in table Q1.4.…”
Section: Resultsmentioning
confidence: 99%
“… 6 Pericardiocentesis guided by echocardiography can be successfully performed over 95% of the time and may reduce both the “door to pericardiocentesis time” and hospital length of stay. 8 , 9 , 10 Despite various success rates, the “blind” approach remains common, especially in emergency situations. Computed tomography models estimate the success rate of the blind approach can be as high as 87% using the subxiphoid approach but much lower (∼60%) using the apical approach.…”
Section: Discussionmentioning
confidence: 99%